1999
DOI: 10.1038/sj.leu.2401258
|View full text |Cite
|
Sign up to set email alerts
|

The role of TEL fusion genes in pediatric leukemias

Abstract: The TEL and AML1 genes are common targets of chromosomal translocations in hematopoietic malignancies. The TEL-AML1 fusion gene, created by the t(12;21), is the most common genetic alteration in childhood acute lymphoblastic leukemia and is associated with a favorable outcome. This review summarizes the roles of the TEL and AML1 proteins in hematopoiesis, the potential transforming mechanisms of TEL fusion proteins, and the clinical significance of the TEL-AML1 fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 45 publications
4
78
0
Order By: Relevance
“…5,6 The ETV6/AML1 fusion transcript is likely to be important for leukemogenesis. 7 Recent reports 1,3,4,8 have shown that this gene rearrangement is associated with a clinically defined subgroup of precursor-B-ALL affecting children with ages from 1 to 12 years who show non-hyperdiploid leukemic lymphoblasts and do not display hyperleukocytosis. Moreover, the presence of the ETV6/AML1 transcript has been found to be associated with a good prognosis since patients with t(12;21) translocation, as compared with other patients, display a higher response rate to chemotherapy.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,6 The ETV6/AML1 fusion transcript is likely to be important for leukemogenesis. 7 Recent reports 1,3,4,8 have shown that this gene rearrangement is associated with a clinically defined subgroup of precursor-B-ALL affecting children with ages from 1 to 12 years who show non-hyperdiploid leukemic lymphoblasts and do not display hyperleukocytosis. Moreover, the presence of the ETV6/AML1 transcript has been found to be associated with a good prognosis since patients with t(12;21) translocation, as compared with other patients, display a higher response rate to chemotherapy.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4] The molecular consequence of the t(12;21)(p13;q22) translocation is the fusion of two known genes named ETV6, mapped to 12p13, and AML1, located at 21q22. This translocation results in the transcription of a chimeric protein which consists of the helix-loop-helix domain of ETV6 and the entire AML1 gene, including both its DNA binding and transactivation domains.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these abnormalities induce the expression of fusion proteins between TEL sequences and amino-acid sequences encoded by the partner gene (Rubnitz et al, 1999;Salomon-Nguyen et al, 2000 and references therein). The largest class of TEL's partner genes encodes protein tyrosine kinases whose catalytic domains are fused to the amino-terminal part of TEL.…”
Section: Introductionmentioning
confidence: 99%
“…The CBFA2 gene translocations include the t(8;21) CBFA2/ETO, associated with *15% acute myeloid leukaemia, the t(3;21) observed in some cases of chronic myeloid leukaemia and more rarely in therapy-related leukaemias and myelodysplasias (reviewed in Nucifora et al, 1995) and the t(12;21) TEL/CBFA2 translocation frequently found in both childhood and adult pre-B acute lymphocytic leukaemia (reviewed in Rubnitz et al, 1999). The CBFB subunit is also disrupted by both inversion and gene deletion in acute myeloid leukaemia (Liu et al, 1993).…”
Section: Introductionmentioning
confidence: 99%